2023
DOI: 10.7759/cureus.47813
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Benefits of Resistance Training in Patients With Heart Failure With Reduced Ejection Fraction: A Systematic Review

Anirudh Danduboyina,
Binay K Panjiyar,
Saatvika R Borra
et al.

Abstract: Cardiovascular diseases pose a serious problem for health globally. Among these, congestive heart failure is the leading cause of mortality and morbidity worldwide. According to the recent census, heart failure contributes to a huge financial burden annually. Exercise therapy is an integral part of the nonpharmacological management of heart failure. Due to the availability of various types of exercise therapies and rapid advancements in the existing evidence, it is often challenging to prescribe an appropriate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Resistance exercise has its advantages over intervention and drugs in terms of cost-effectiveness and continuity of efficacy (57). A systematic evaluation study showed that an exercise regimen that integrated resistance training with aerobic exercise yielded greater cardiovascular benefits than aerobic exercise alone (58). In addition to the above exercises, high-intensity interval training (HIIT) has also been recommended for patients with stable cardiovascular disease and has been suggested to provide additional benefits (59).…”
Section: Exercise Prescription For Cardiac Rehabilitationmentioning
confidence: 99%
“…Resistance exercise has its advantages over intervention and drugs in terms of cost-effectiveness and continuity of efficacy (57). A systematic evaluation study showed that an exercise regimen that integrated resistance training with aerobic exercise yielded greater cardiovascular benefits than aerobic exercise alone (58). In addition to the above exercises, high-intensity interval training (HIIT) has also been recommended for patients with stable cardiovascular disease and has been suggested to provide additional benefits (59).…”
Section: Exercise Prescription For Cardiac Rehabilitationmentioning
confidence: 99%